The chocolate pirate plot [large type] - Carl, JoAnna (Carl, JoAnna. Chocoholic mystery., 2011)
When Young Blackbeard became the biggest movie of the decade, the residents of Warner Pier caught pirate fever. TenHuis Chocolade is raking in the booty selling chocolate treasure chests. And in what comes to be known as the Summer of the Warner Pier Pirates, a mischievous band of costumed pirates starts boarding boats on the lake and performing a sea chantey before departing. The town couldn't be more amused - until a body washes up on shore.